Investigations into Feed Value of Hippomarathrum microcarpum (Bieb) Fedtsch silages - Sevilay GÜL (ISPEC Journal of Agricultural Sciences)
The aim of this study was to determine chemical composition, in vitro organic matter digestibility and energy contents of H. microcarpum silage. H. microcarpum was harvested  at growing stage. Forage was chopped and divided into trial two groups for the control and 5% molasses. H. microcarpum ensiled in special 1.0 liter anaerobic jars. Chemical and in vitro cellulase method were conducted on the silage which was opened on the 60th day of storage.  According to the analysis of the control, 5% mollases treatments, dry matter reached 18.97%, 23.41% and metabolisable energy reached 7.65, 9.81 MJ/kg KM; while organic matter digestibility was 55.50% and 72.35%, respectively. In conclusion, addition of molasses can increase dry matter content and organic matter digestibility of canola silage.